An Analysis of Speech Act Used in Matilda Wormwood (1996) Movie - Septiawan, Kadek Yudha; Tantra, Dewa Komang; Ramendra, Dewa Putu (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-JulyDO - 10.24843/e-jl.2022.v16.i02.p14, 2022)
This research aimed at analyzing the speech act performed by the characters in Matilda Wormwood movie. This study was carried out in the form of a descriptive qualitative study. The major data sources were utterances in the Matilda Wormwood movie. The movie screenplay was also employed as a supplementary source in this research. The data were obtained using observation and documentation procedures, and they were evaluated using the steps of data condensation, data presentation, and conclusion drafting. The research findings revealed that utterances employed in the form of the locutionary act, the type of the illocutionary act, and classification of speech act. The most dominant the locutionary act utilized by the research subject is a declarative form, which consisted of 37% of the total data. Then, the most prevalent the illocutionary act used by the research subject is a representative type, which consisted of 36% of the total data. Since the form and type of the research subject's most prominent speech act are relevant. Furthermore, the research subject's utterances are frequently given directly in sequence, which Yule's theory refers to as a direct speech act. This research increased the knowledge and comprehension of the many forms and types of speech act in society purposes of language.